Parasitismo y desarrollo de Trichogramma exiguum Pinto & Platner y Telenomus sphingis (Ashm) sobre Erinnyis ello (L.) - Urias López, Mario Alfonso; Bellotti, Anthony C. (1989)
The parasitism, development, and thermal requirements of Trichogramma exiguum and Telenomus sphingis, common parasitoids of Erinnyis ello eggs, were studied. Life statistics were also determined for each specie and temp. (20, 25, and 30 degrees C for both species; for T. sphingis 32.5 degrees C was also used). Greatest fecundity of T. exiguum females occurred at 20 and 25 degrees C, but a smaller no. of females parasitized eggs at 20 degrees C. A more favorable sex ratio of T. exiguum was found at 25 and 30 degrees C. Greatest fecundity of T. sphingis occurred at 25 and 30 degrees C; at these temp. the sex ratio was unaltered. The highest development rate of both species occurred at 30 degrees C; the min. threshold values for T. exiguum and T. sphingis were 13.5 and 14.2 degrees C, resp., and the resp. physiological time was 95.6 and 123.1 degrees day. T. exiguum had no max. threshold value, but for T. sphingis this value was 30 degrees C. Optimum population growth occurred at 25 degrees C for both species; T. exiguum was more efficient in parasitizing E. ello eggs than T. sphingis. (CIAT)